ANALISIS PENGGUNAAN KONJUNGSI DALAM SKRIPSI MAHASISWA PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS EKASAKTI - Khairani, Zuraida; Marisya, Susanti (STKIP Pesisir Selatan, 2024)
This study is motivated by the assumption of students who say that the use of conjunctions is easy and trivial. Learning about conjunctions is taught together with several other language skills learning such as writing and reading. Learning is more focused on learning language skills only. Meanwhile, linguistic rules are often neglected in learning. The purpose of this research is to analyze the use of conjunctions in the theses of students of Indonesian language and literature education program of Ekasakti University. This research is a descriptive qualitative research. The data in this study are conjunctions used in the theses of students at Ekasakti University. The data collection technique in this research is a document search technique. Through documents. Data analysis is carried out by data reduction, data presentation with the help of data recording tables, and drawing conclusions. Data validity is carried out by triangulating sources and theories, namely testing the validity of data using theories and sources relevant to the object. The result shows that there is an inaccurate use of conjunction in the thesis of Ekasakti University students. The inaccurate use of conjunctions is mostly found in the use of subordinative conjunctions. Students are not able to place the conjunction according to the function of the conjunction. Even students have not fully paid attention to the difference in writing conjunctions within sentences and between sentences.